A Distributed Electric Vehicle Charging Scheduling Platform Considering Aggregators Coordination - Shahab Afshar (IEEE, 2021)
In this paper, a two-layer distributed optimization platform employing the alternating direction method of multipliers (ADMM) method is developed as an exchange problem to solve the electric vehicle charging management problem (EVCMP). The proposed model establishes a coordination layer between the EV aggregators, which increases the optimization’s overall efficiency while preserving aggregators’ independence. Numerical tests validate that the proposed coordinated distributed platform (CDP) enhances the load profile’s smoothness compared to the locally coordinated and uncoordinated charging platforms. Moreover, CDP also decreases the total EV charging costs by 35%, compared to the uncoordinated charging approach.